MAPPING THE POTENTIAL AND DEVELOPMENT OF INDEPENDENT CATEGORY VILLAGES IN BOGOR REGENCY - Amelia Rahmi (Research Collaboration Community (RCC), 2023)
Independent villages are villages that have sufficient availability and access to essential services, adequate infrastructure, accessibility/transportation that is not difficult, good public services, and an already excellent administration. However, not all independent villages are able to be independent in all aspects. The ranking of village categories is based on social, economic, and social aspects. This study aims to determine the ranking of independent category village villages on different size scales and find out which villages are superior in every social, economic, and social. This study used RapidMiner to determine the ranking of independent villages and cobwebs as a mapping of the advantages of each dimension. The results of this study were obtained from 14 villages that belong to the high-independent category. From these fourteen villages, the results of mapping using cobwebs for each dimension were obtained. The mapping results show that one village excels in two dimensions, namely Bojonggede Village, in the economic and social dimensions. Meanwhile, in the ecological dimension, Sukahati Village is a superior village. Suppose you look at the advantages of each dimension, then for the first dimension, namely the economic dimension. In that case, there are five superior villages, including Tajur, Limusnunggal, Cileungsi, Pondok Udik, Bojonggede, Cibanteng, and Gunungsari Villages. The second dimension is the social dimension; one village looks superior, Bojonggede Village. Finally, in the ecological dimension, the superior village is Sukahati Village.